Single nucleotide polymorphisms in TaER genes and their association with carbon isotope discrimination in wheat genotypes under drought - T. A. Yasir; H. Ali; A. Wasaya; H. M. Aatif; M. Hussain; M. Farooq; A. W. Baloch; Y. G. Hu (Biologia Plantarum, 2018)
Candidate gene association studies implicate the detection of contributing single nucleotide polymorphism (SNP) for the target traits and have been recommended as a promising technique to anatomize the complex characters in plants. ERECTA gene in plants controls different physiological functions. In this study, we identified SNPs in 1.1 kb partial sequences of TaER-1 and TaER-2 of wheat (Triticum aestivum L.). Thirty-nine SNPs were identified in the coding regions of TaER-1 gene in 33 wheat genotypes, of which 20 SNPs caused non-synonymous mutations while 19 SNPs produced synonymous mutations; while 31 SNPs were located in the coding regions of TaER-2 gene in 26 genotypes, of which 18 SNPs caused non-synonymous mutations and 13 SNPs caused synonymous mutations. In addition, 32 SNPs in TaER-1 and 9 SNPs in TaER-2 were also identified in the non-coding regions. Moreover, the significant genetic associations of SNPs of TaER-1 and TaER-2 genes with carbon isotope discrimination, stomatal conductance, photosynthetic rate, transpiration rate, intrinsic water use efficiency (iWUE), leaf length, leaf width, stomatal density, epidermal cell density, and stomatal index were noted in wheat genotypes. This study confirms the importance of TaER-1 and TaER-2 genes which could improve iWUE of wheat by regulating leaf gas exchange and leaf structural traits. These identified SNPs may play a critical role in molecular breeding by means of marker-assisted selection.